AN OBLIQUE CONVERGENCE AND ROTATION MODEL FOR THE EMPLACEMENT OF THEBAFT OPHIOLITIC MÉLANGE IN IRAN - Babaei, Abbed; Arvin, Mohsen; Babaie, Hassan A. (Ofioliti, 2001)
The Late Cretaceous -Early Tertiary Baft ophiolite sequence in central Iran is a part of the Mesozoic ophiolitic belt that surrounds the Central Iranian Microcontinent (CIM) for several hundred kilometers. The ophiolitic complex includes blocks of gabbro, hypabyssal rocks, and spilite (both as lava flows and pillow lavas) enveloped in a matrix of tectonized harzburgite. Geochemical studies reveal two mafic lava groups, a tholeiitic basalt, which is similar to mid-oceanic ridge basalt, and a transitional tholeiitic basalt similar to intra-plate basalt. Geological observations and chemical analyses suggest that the Baft ophiolite might have formed at or near a ridge-transform intersection in a small, slow spreading (<1 cm/year) oceanic basin (Nain-Baft basin). This ophiolite was emplaced on the Central Iranian Microcontinent due to oblique convergence of the Afro-Arabian Plate with Eurasia. Slow spreading of the basin is suggested by the absence of cumulate gabbro and lack of evidence for pure melt segregation of magma. Support for the oblique convergence and for a counter-clockwise rotation of the spreading system includes (1) the juxtaposition of the metamorphic complex of eastern Central Iranian Microcontinent with the metamorphic belt of southern Iran (Sanandaj-Sirjan Belt) to the west and (2) the intersection of the older, north-south trending doleritic dikes with younger, east-west trending doleritic dikes. The sheared contacts between different lithological units, the development of a pronounced schistose foliation at the contact between serpentinized harzburgite and gabbro, as well as sheared clasts and dismembered rocks within basalt and serpentinized peridotite, are further evidence for the oblique convergence model.